The Intelligence-Led Risk Management for National Security sand Public Safety in Nigeria: Strengthening the Collaborative Continuum for Optimum Efficiency - Daniel Nte, Ngboawaji; Nathaniel Nte, Ucheawaji (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2025)
Abstract:Risk management has remained one the basic pivots of national security. For a country like Nigeria battling with myriads of national security and public safety threats such as; terrorism, insurgency, urban crime, critical infrastructure sabotage, natural hazards, pandemics etc., the need to strategically integrate the efforts of both the intelligence and risks analysts cannot be overemphasised. This work therefore strongly advocates a functionally decentralised collaboration between all the relevant stake holders in national security management. The work therefore advocates for a fusion of both intelligence and risk management in the business of managing both national security and public safety in ways that will institutionalise a sustainable risk management culture in an ever dynamic world and Nigeria in particular.